2022
DOI: 10.17583/ijelm.7966
|View full text |Cite
|
Sign up to set email alerts
|

Leadership approaches of principals heading National Strategy Learner Attainment Schools in South Africa

Abstract: This study examines the leadership approaches associated with sustained improved academic performance of principals heading National Strategy for Learner Attainment (NSLA) schools. This article reports on a qualitative multiple-case study focused on five successful NSLA secondary schools in Cape Town, South Africa. Data was collected from principals, teachers and selected School Management Team (SMT) members via questionnaires and semi-structured interviews to understand the leadership practices and personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This result shows that the research objectives and research hypotheses can be answered. It is also consistent with the research of many people, such as the research of Gottfredson and Reina (2020), the research of Vilkinas, Murray, and Chua (2020), the research of Cornelissen and Smith (2022), the research of Parinyamit, Chaiya, Wattana, and Surat ( 2017), the research of Kusuman (2020), the research of Siriphong (2021) and the research of Supawat, Natjaree, and Chusak (2021) that concluded leadership styles are related to and influence management and organizational performance.…”
Section: Discuss the Results Of Component Analysis And Study Of Direc...supporting
confidence: 84%
“…This result shows that the research objectives and research hypotheses can be answered. It is also consistent with the research of many people, such as the research of Gottfredson and Reina (2020), the research of Vilkinas, Murray, and Chua (2020), the research of Cornelissen and Smith (2022), the research of Parinyamit, Chaiya, Wattana, and Surat ( 2017), the research of Kusuman (2020), the research of Siriphong (2021) and the research of Supawat, Natjaree, and Chusak (2021) that concluded leadership styles are related to and influence management and organizational performance.…”
Section: Discuss the Results Of Component Analysis And Study Of Direc...supporting
confidence: 84%
“…Moreover, recent studies support the use of leadership skills to influence followers or subordinates and to enhance service delivery in organisations (Cornelissen and Smith 2022;Fang et al 2019;Inderjeet and Scheepers 2022). This study is based on the behavioural theory of leadership, which states that a leader's success is determined by his or her behaviour (Northouse 2021).…”
Section: The Literature Reviewmentioning
confidence: 99%
“…The mood or response of group members to a leader with complete authority will differ from that of group members to a leader with little or no management (Samsu, 2022). Although numerous credible findings link individual attributes to leadership effectiveness, this approach to understanding leadership is of limited utility because many traits cannot be examined (Cornelissen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%